A comparison of capillary electrophoresis and next-generation sequencing in the detection of immunoglobulin heavy chain H and light chain κ gene rearrangements in the diagnosis of classic hodgkin's lymphoma. Issue 3 (1st March 2022) - Zhang, Juan-Juan; Xie, Yu-Xin; Luo, Li-Lin; Yang, Xuan-Tao; Wang, Yi-Xing; Cao, Yue; Long, Zheng-Bo; Wang, Wan-Pu
ABSTRACT: This study aimed to compare the application value of capillary electrophoresis and next-generation sequencing for immunoglobulin (IG) gene rearrangement in the diagnosis of classic Hodgkin's lymphoma. Twenty paraffin-embedded specimens from patients with classic Hodgkin's lymphoma were screened. For gene rearrangement detection, the ABI 3500 Genetic Analyzer and ABI Ion GeneStudio S5 Plus sequencing system were used, respectively, and the results were compared. Five cases with monoclonal rearrangements (25%, 5/20) were detected by Capillary Electrophoresis, and positivity for the FR1, FR2, FR3, and IGк loci was 5%, 10%, 10%, and 15%, respectively; 12 cases with monoclonal rearrangements (60%, 12/20) were detected by Next-generation Sequencing where the positivity of the above corresponding loci were 35%, 45%, 50%, and 30%, respectively. Among the 20 samples, 6 IGк clonal rearrangements were detected, and the usage frequency (66.7%) of IGкJ4 was the highest in the IGкJ subgroup. The usage frequency of IGкV1 and IGкV3 in the GкV sub-group was 33.3% and 33.3%, respectively. Twelve immunoglobulin heavy chain (IGH) clonal rearrangements were detected among the 20 samples, and the order of usage frequency in the IGH joining region J (IGHJ) subgroup was IGHJ4 > IGHJ5 > IGHJ6 > IGHJ3. The gene with the highest usage frequency in the IGH variable (IGHV) subgroup was IGHV3 (50%) and the percentage of IGHV mutations ranged from 0% ± 11.45% with an average frequency of 3.34%. Compared with Capillary Electrophoresis, Next-generation Sequencing showed a higher positivity in the detection of gene clonal rearrangements, was more accurate in the interpretation of results. Graphical abstract: uf0001